Ventral Stabilization of a T2-T3 Vertebral Luxation via Median Sternotomy in a Dog - Sarah Klatzkow; Matthew D. Johnson; Michele James; Sheila Carrera-Justiz (Case Reports in Veterinary Medicine)
An 8-year-old neutered male miniature Poodle presented for evaluation of a suspected T3-L3 lesion with cervical component following vehicular trauma. Magnetic resonance imaging and computed tomography revealed a T2-T3 luxation with right displacement of T3. A T2 caudal endplate fracture was present as well as multifocal noncompressive bulges of cervical intervertebral discs. Conservative management failed and ventral stabilization of C7-T4 was performed via a median sternotomy. Paired String-of-Pearls plates were placed on the ventral aspect of vertebrae. Eight weeks postoperatively, the dog was ambulatory with moderate pelvic limb paraparesis. A luxation of T2-T3 is uncommon in small animals and surgical stabilization is poorly described in literature. This case report demonstrates the use of a ventral approach to cranial thoracic vertebral stabilization with a successful outcome.